An Analysis of Corporate Strategy Formulation for Micro, Small, and Medium Enterprises (MSMEs): A Case Study of the Kerupuk Industry in Tlasih Village, Tulangan District, Sidoarjo, East Java - Lestari, Lestari; Erdiana, Atty; Giyana, Giyana (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to formulate a corporate strategy for small-scale industry (MSME) producers of kerupuk (traditional crackers) in Tlasih Village, Tulangan District, Sidoarjo Regency, East Java. The research object is an MSME with a formal organizational structure, where corporate decision-making is carried out through managerial considerations. The general objective of this study is to identify the internal conditions of the MSME in order to determine its strengths and competitive advantages, as well as its relative weaknesses. In parallel, the study identifies changes in the external environment so that the MSME can detect both the opportunities and threats it faces. Through this analysis, the MSME Kerupuk Tlasih can formulate appropriate strategies from various strategic alternatives to remain competitive under such conditions. The specific objective of the study is to provide recommendations for the most effective corporate strategy that will enable the MSME Kerupuk Tlasih to sustain its operations amid environmental and competitive changes. The selection of MSME Kerupuk Tlasih as the research object given its formal organizational structure aims to allow for a clear assessment of its relative condition and the extent of its strengths and weaknesses in responding to environmental dynamics. This MSME is expected to leverage its strengths to capitalize on external opportunities and mitigate threats arising from environmental shifts. The analytical models employed in this study include the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and SWOT analysis. The results indicate that the SWOT analysis places MSME Kerupuk Tlasih in Quadrant II, illustrating that the enterprise is currently facing significant external threats while maintaining relatively strong internal capabilities. Consequently, the most appropriate strategies for MSME Kerupuk Tlasih are market development and product development strategies.